﻿Explore Adverse Drug Reactions (ADRs) reporting by clinical and community pharmacists in Duhok, Kurdistan region- Iraq: hampered and perspective - Omer Allela (Pensoft Publishers, 2022)
Background: Pharmacovigilance systems are crucial for monitoring, ensuring the safe use of medications, and reducing the frequency of adverse drug reactions (ADRs). They also raise awareness of the importance of reporting ADRs to healthcare systems. Aim: Explore the hampered and perspective held by Duhok pharmacists, particularly those employed in hospitals and private pharmacy sectors, about pharmacovigilance and ADR reporting. Methods: A cross-sectional study was carried out from 20 February to 20 March 2019 using a self-administered questionnaire that had been previously created and modified. The data were examined using SPSS version 20, a statistical application for social software. Results: The majority of respondents, pharmacists, stated that it is their responsibility to report adverse drug reactions (ADRs), and that drug safety monitoring is crucial (91%). More than 85% of pharmacists agreed that ADRs that result in life-threatening situations and those that result in congenital abnormalities should be reported immediately. The majority of them, however, were unaware of the Iraqi pharmacovigilance system, had never reported any adverse drug reactions, were unable to get reporting forms, and lacked the clinical knowledge required to recognize ADRs. Conclusion: Underreporting was the main issue identified by the study because the majority of respondents were unable to define the term "pharmacovigilance" correctly, but they were aware of ADRs and displayed a positive attitude toward ADR reporting despite the fact that the majority of them had never reported any ADRs. To raise pharmacists' knowledge and awareness of the ADR reporting procedure, however, required steps should be made to establish interventional programs.